Factors affecting purchase intention among undergraduate student on mobile shopping websites - Badrul Hisham, Farah Nadhirah (2020)
The purpose of this study was to determine the factors affecting purchase intention among undergraduate student on mobile shopping websites. The variable consists of quality of service, security and privacy policies, satisfaction and trust. The finding showed that quality of service, security and privacy policies, satisfaction and trust have influence on the purchase intention among undergraduate student on mobile shopping websites. All variables showed significant relationship towards the factors that affecting purchase intention among undergraduate student on mobile shopping websites. The study refers to the primary data and secondary data for supporting the sampling techniques. Meanwhile, the researcher use questionnaire as the method to collect all the data from sample of respondents in accomplishing the research objectives. The data collected and analyzed for this study by using mean point value, standard deviation and correlation analysis. The result of this study that was presented in this research seems agrees that quality of service, security and privacy policies, satisfaction and trust can influence purchase intention among undergraduate student on mobile shopping websites. This study can be seen as a foreword to more detailed study that can be carrying by future research on the issue of the factors affecting purchase intention among undergraduate student on mobile shopping websites.